Sero-epidemiology of measles immunoglobulin G antibodies among newborns from South-East Asia and sub-Saharan Africa: an observational, multicenter study - Carine Bokop; Nisha Dhar; Alane Izu; Musa Mohammed Ali; Godwin Akaba; Hellen C. Barsosio; James A Berkley; Manisha Madhai Beck; Tolossa E Chaka; Clare L. Cutland; Phurb Dorji; Adama Mamby Keita; et al. (International Journal of Infectious Diseases)
Objectives: To investigate the transplacental acquisition of measles immunoglobulin (Ig)G in newborns at delivery in Bangladesh, Bhutan, India, Ethiopia, Mozambique, Kenya, Nigeria, Mali, and South Africa. Methods: Archived cord serum, from a multicenter study on Group B Streptococcus, were tested for measles IgG using a commercial enzyme link immunosorbent assay (ELISA). We tested 323 randomly selected samples from each of the sites. Models using various measles antibody decay rates in infancy were explored. Results: Overall, 2,907 cord serum samples were analyzed. At birth, 49.9% of newborns were measles IgG seronegative. Measles seronegativity ranged from 21.7% in Nigeria to 73.4% in Bhutan. The adjusted odds of seronegativity in infants of mothers born after measles vaccination implementation was 1.78 times that for infants born to unvaccinated mothers (adjusted odds ratio 1.78; 95% confidence interval 1.43-2.21; P <0.001). Modeling measles-IgG kinetics predicted that 70.8%, 88.3%, and 100% of infants would be seronegative by 2, 4, and 6 months, respectively, without further exposure. Conclusions: Our findings suggest low transplacental acquisition of measles IgG in newborns, which is likely to yield susceptibility to measles infection at a very young age. The currently recommended measles vaccine schedules in low- and middle-income countries (LMICs), with the first dose recommended from 9 months of age and onward, warrant reconsideration, including the need for earlier dosing schedules.